Defense Mechanism as a Strategy to Overcome Jacob's Anxiety in William Landay's Defending Jacob - Annisa Febriana; Diana Budi Darma (Universitas Cokroaminoto Palopo, 2022)
Defense mechanism is a strategy or effort developed by the ego to dispel unpleasant feelings caused by anxiety so that unpleasant feelings and experiences feel better. The purpose of the study are to reveal the type of anxiety experienced by Jacob Barber in William Landay's Defending Jacob and discover how defense mechanisms work to overcome this anxiety. The method used in this study is qualitative by applying Sigmund Freud's anxiety and defense mechanism theory in a psychoanalytic approach. The data in this study are in the form of phrases, sentences, and dialogues contained in the novel Defending Jacob written by William Landay. The results of this study indicate that there are three types of anxiety experienced by Jacob Barber. They are neurotic, moral, and realistic anxiety. In order to overcome these anxiety, Jacob Barber uses five types of defense mechanisms, namely denial, projection, displacement, rationalization, and reaction formation. The types of defense mechanisms that are most often used to overcome the anxiety that arise in Jacob Barber are projection and displacement.